Bacterial population and chemicals in bioaerosols from indoor environment: Sludge dewatering houses in nine municipal wastewater treatment plants - Han, Yunping; Wang, Yanjie; Li, Lin; Xu, Guangsu; Liu, Junxin; Yang, Kaixiong (The Science of the total environment, 2018)
•Chemical and bacterial properties in sludge dewatering house were analyzed.•Levels of airborne bacteria and chemicals showed regional variations.•Bacterial population in bioaerosols also presented significant regional disparity.•Common potential pathogens were detected in bioaerosols from all SDHs.•RH and temperature were major parameters on bioaerosols to survive in SDHs. [Display omitted] Municipal wastewater treatment plants (MWTPs) are regarded as sources of airborne microorganisms. Sludge dewatering house (SDH) is one of the most serious indoor bioaerosol pollution treatment sectors in MWTPs. In this study, properties of bioaerosols from SDHs of nine MWTPs were investigated in China. Results suggested that bioaerosols were generated mainly from the mixed liquor and will be promoted by the mechanical motion of belts of dewatering devices. They will accumulate in the SDHs due to the treatment devices placed inside. Levels of airborne bacteria and chemicals showed regional variations. In Hefei and Yixing, the emissions of total suspended particles (TSP) and airborne bacteria were higher than those in Beijing and Guangzhou. Results of bacterial population showed that bacterial species in bioaerosols from SDHs also presented significant regional disparity; these regional disparities were closely related with the source of bioaerosols in SDHs. Among these identified bacterial species, some common potential pathogens were detected in all SDHs, such as Aeromonas caviae, Flavobacterium sp., and Staphylococcus lentus. Relative humidity (RH) and temperature were the major parameters on bioaerosols to survive. As shown in this study, SDHs in wastewater treatment plants should be provided considerable attention for being an emission source of indoor bioaerosols.